Spatial and temporal variations in trophic connectivity within an estuarine environment : benthic-pelagic and terrestrial-aquatic linkages via invertebrates and fishes - Bergamino Roman, Leandro (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2015)
Estuarine ecosystems are among the most biologically productive areas and they provide important ecosystem services such as erosion control, habitat and refugia for several species. These environments are characterized by the presence of a variety of organic matter sources due to their transitional position between rivers and the sea. The biotic compositions can undergo spatial and seasonal changes along the estuary due to the spatial and temporal fluctuations of environmental factors such as salinity, temperature and seston loads. Therefore, the different combinations of biotic and abiotic factors make each estuary a unique ecosystem. Because of this spatial and temporal complexity, the understanding of estuarine food web structure and which factors affect the trophic relationships within the ecosystem through space and time represent challenging tasks. Furthermore, estuaries are under an increasing number of anthropogenic perturbations because of the growing concentration of human populations in coastal areas. Knowledge of ecosystem structure and functioning is essential for effective conservation and management planning of coastal areas.In this dissertation, I combine the utilization of biological tracers to examine spatial and temporal variability in the food web structure within a small temperate and microtidal estuary located in South Africa. To this end, fatty acid profiles and stable isotope signatures were measured in several primary organic matter sources and consumers (including zooplankton, fishes and benthic invertebrates) during four consecutive seasons and in three different estuarine regions: upper, middle, and lower reaches. The three reaches had distinct habitat features of vegetation type and morphology, and in particular the lower reaches were colonized by the marsh grass Spartina maritima. Isotopic mixing models were used to estimate the relative contribution of each food source to the diets of invertebrates and fishes within the estuarine food web. The isotopic and fatty acid data showed similar results. In general, the lower reaches of the estuary were characterized by a higher deposition and assimilation by brachyuran crabs of carbon derived from marsh grass detritus, whiletowards the upper reaches a mixture of microphytobenthos and particulate organic matter (phytoplankton and detritus) was deposited and sustained the pelagic and benthic fauna. The highest deposition and assimilation of marsh grass detritus in the lower reaches of the estuary occurred during periods of low freshwater discharge (autumn and winter). In the upper reaches, microphytobenthos and suspended particulate organic matter were dominant basal food resources for the food web during all seasons. These results indicated that benthic consumers incorporated mainly local carbon sources from their local habitat.To clarify isotopic and fatty acid patterns I examined the trophic behaviour of the sesarmid crab Sesarma catenata through laboratory feeding experiments. Results from these experiments validated that decomposed leaves of riparian trees and the salt marsh plant S. maritima were the preferred food of the sesarmid crabs, potentially due to high bacterial loads. The remaining leaf material not assimilated by crabs, together with faecal material, are likely important subsidies for adjacent environments, hence representing an important energy pathway involving the microbial food chain. Furthermore, this dissertation showed the importance of mobile top predators as vectors energetically connecting distinct food chains within the estuary (i.e. littoral, benthic and pelagic). I concluded that a combination of physical (i.e. patterns of freshwater discharge and estuary morphology) and biological factors (i.e. organism feeding behaviour, mobility, primary productivity, the local vegetation type) influence the pattern of dominant primary organic matter sources, and therefore the food web structure along the estuarine environment. In particular, marsh grass detritus contributed substantially to the diets of estuarine fauna during periods of low freshwater discharge. Given the importance of the salt marsh habitat in providing trophic resources, it is important to preserve this environment to sustain the natural biota and ecosystem functioning.
Keywords: Estuarine ecology -- South Africa; Marine invertebrates -- South Africa -- Ecology